The Rise of Shared Work Spaces: A Disruption to Urban Planning Policy? - Babb, C.; Curtis, Carey; McLeod, S. (Routledge, 2018)
New models of shared work spaces have the potential to disrupt planning for traditional employment spaces.  Drawing on a pilot study of Greater Perth and regional Western Australia, relevant planning policies and interviews with a sample of managers and users of shared work spaces are reported. Shared work spaces are emerging in regulatory voids left by outdated policy frameworks, instead relying on the forward thinking of local innovators seeking to revitalise urban centres. The success of innovative repurposing of space brings into question the efficacy and purpose of more prescriptive land use regulations and policies.